Suitability of Spring Water Quality for Community Utilization in Girijati Village, Gunungkidul - Alifia , Najma; Ilyas, Tasya Annisa Ramadanti; Putri, Ivanya; Salshabila, Amanda Azra; Utami, Aulia Rahma; Ardiansyah, Muhammad Farrel; Lestari, Filya Rizky (Jurnal Penelitian Geografi, 2025)
Springs are natural water sources that play an important role in meeting community needs; however, their quality must be considered to ensure safe utilization. This study aims to evaluate and compare the water quality of Mudal and Sendang Beji Springs in Girijati Village, Purwosari Subdistrict, Gunungkidul Regency, based on basic physical and chemical parameters in relation to their local uses. The research employed a descriptive quantitative method with comparative analysis, in which water samples were collected on May 13–14, 2025, and analyzed using physical parameters (temperature, TDS, taste, odor) and chemical parameter (pH). The results were then compared with the Indonesian Ministry of Health Regulation No. 32 of 2017 concerning hygiene, sanitation, and public bathing standards. Findings indicate that Mudal Spring has an average temperature of 27.83 °C, TDS of 425.67 mg/l, pH of 6.78, is odorless, and has a fresh taste. Meanwhile, Sendang Beji Spring shows a pH of 6.67 with similar physical characteristics. All measured parameters meet the quality standards for hygiene, sanitation, and public bathing purposes. It can be concluded that both springs are suitable for daily community needs such as drinking, bathing, washing, and agricultural irrigation in accordance with their current utilization.